2018
DOI: 10.1128/jcm.00717-18
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Evaluation of the Etest Gradient Diffusion Method for Ceftolozane-Tazobactam Susceptibility Testing of Enterobacteriaceae and Pseudomonas aeruginosa

Abstract: Ceftolozane-tazobactam (C/T) is a novel beta-lactam-beta-lactamase inhibitor combination antibiotic approved by the U.S. Food and Drug Administration in 2014 for the treatment of complicated intra-abdominal infections (in combination with metronidazole) and complicated urinary tract infections. In this study, we evaluated the performance of the C/T Etest, a gradient diffusion method. C/T Etest was compared to broth microdilution (BMD) for 51 challenge isolates and 39 challenge isolates at three clinical sites.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…As far as the P. aeruginosa isolates, the C/T Etest yielded excellent results, which were similar to those previously found in a multicenter evaluation using the EUCAST breakpoint [29]. On the contrary, Daragon et al reported higher VME (5.0% and 25.0% when the total number and the number of C/T-resistant isolates were used as the denominator for calculation, respectively) due to a high proportion of strains (19.5%) had C/T MICs close to the EUCAST breakpoint [19].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…As far as the P. aeruginosa isolates, the C/T Etest yielded excellent results, which were similar to those previously found in a multicenter evaluation using the EUCAST breakpoint [29]. On the contrary, Daragon et al reported higher VME (5.0% and 25.0% when the total number and the number of C/T-resistant isolates were used as the denominator for calculation, respectively) due to a high proportion of strains (19.5%) had C/T MICs close to the EUCAST breakpoint [19].…”
Section: Discussionsupporting
confidence: 84%
“…On the contrary, Daragon et al reported higher VME (5.0% and 25.0% when the total number and the number of C/T-resistant isolates were used as the denominator for calculation, respectively) due to a high proportion of strains (19.5%) had C/T MICs close to the EUCAST breakpoint [19]. Following the CLSI criteria, previous studies have also confirmed the excellent performance of C/T Etest strips when applied to P. aeruginosa [27,29,30].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…P. aeruginosa was classified as MDR or XDR, as previously defined [20]. C/T susceptibility was determined by e-test [21]. The strain was classified as susceptible if the C/T MIC was ≤4 mg/L, according to the European Committee on Antimicrobial Susceptibility Testing (EUCAST).…”
Section: Methodsmentioning
confidence: 99%
“…All ETEST strips evaluated in this study are cleared by FDA 510 k guidance for P. aeruginosa. Specific to the newer agents, CZA and C/T, a number of studies have reported acceptable performance for ETEST relative to reference BMD [21][22][23][24][25][26]. Notably, none of these studies reported inclusion of CF isolates, which not only may have higher rates of antibiotic resistance, but also more likely to overexpress the alginate exopolysaccharide, develop biofilms, and have a number of unique growth characteristics and phenotypes [27,28].…”
Section: Discussionmentioning
confidence: 99%